Modification of the micromotor head for a new surgical guide for implants: a case study - Gamarra Ojeda, Roxana (2022)
Surgical guides are essential devices for the proper placement of dental implants, being the computer generated surgical guide the most precise, its guide plane is at the level of the shaping drill, this new surgical guide has the guide plane at the level of the head of the micromotor, it is restrictive in the mesiodistal and vestibule / palatine-lingual directions, it has the advantage that it does not interfere with the cooling of the drill, it adapts to all implant systems, it does not require an additional kit. For the manufacture of said guide, the head of the micromotor must be modified by adding an element that will allow it to have 3 walls joined at a 90-degree angle, and on this the guide rail will be positioned, which will direct the shaping drills of the bone bed in the bone thickness of the alveolar ridge indicated by tomography and reverse planning. In 8 patients who required an implant, the proposed guide was used, and in another 8 the implant was placed with the freehand technique. With the proposed guide, it showed deviations that ranged from 0 mm to 0.61 mm; The deviations with the freehand technique were in the range of 0.58 to 1.56 mm. Statistically there was no significant difference. The main advantage of this guide is that it allows adequate cooling of the implant bed-forming drill, a new surgical kit is not required, it is compatible with any system; Among the disadvantages is that this head must be manufactured for each brand of micromotor, although the guide rail may be the same.